Effectiveness of the guided self-change intervention for reducing alcohol use in adolescents with and without history of cannabis use - Carballo, José Luis; Martínez-León, Miguel Ángel; Coloma-Carmona, Ainhoa; Pérez-Jover, Virtudes; del Castillo-López, Álvaro García; Sancho-Domingo, Clara; Pelegrín-Muñoz, Antonia; van-der Hofstadt-Román, Carlos (Frontiers in Psychology, 2025)
IntroductionThe use of alcohol is a prevalent phenomenon among adolescents. Several brief intervention strategies have been developed to prevent the progression of alcohol use to high-risk levels. The consumer profile, including whether they have consumed one or more substances, may be a key variable in analyzing the effectiveness of interventions.MethodsThis study consists in a secondary analysis of data from a randomized controlled trial (PREVENALC) to examine the effectiveness of a brief intervention based on the Guided Self-Change Program (GSC) and its interaction with substance use profile. Participants were the 629 students in the experimental arm of PREVENALC who received the GSC and completed the pretest, posttest, and 6-moth follow-up measures. The sample was categorized into two groups according to substance use profile: Group of Alcohol Users (GA) (n = 438, 76.8%) and Group of Alcohol and Cannabis Users (GAC) (n = 144, 23.2%). Alcohol consumption (Standard Drinking Units (SDUs), binge episodes and days of abstinence) and problematic drinking were considered as primary variables. Readiness to change and self-efficacy were considered as secondary variables.ResultsOverall, GAC students demonstrated higher rates of alcohol consumption and lower levels of readiness to change at baseline. Both groups reduced the total amount of alcohol, binge drinking episodes and problematic drinking and increased the percentage days of abstinence in the last month. Nevertheless, GAC reduced the amount of alcohol in the last month more significantly than GA. However, the GAC did not maintain improvements in terms of the percentage of days of abstinence in the medium term.DiscussionFuture research should consider substance use profiles when evaluating the efficacy of interventions. Furthermore, large sample designs, control groups and longer follow-ups are required.